2022
DOI: 10.1038/s41598-022-19956-1
|View full text |Cite
|
Sign up to set email alerts
|

A proposed synergetic mechanism for metal fume fever involving ZnO and Fe3O4 nanoparticles

Abstract: Metal fumes fever (MFF) is an inflammatory condition, whose mechanism is yet unclear, associated with the inhalation of metal fumes, particularly zinc. In this study we investigate experimentally the hypothesis of a two-step mechanism of MFF onset: (1) the photocatalytic production of airborne hydrogen peroxide (H2O2) via ZnO and (2) the production of hydroxyl radicals (HOׄ) through Fenton reaction via magnetite (Fe3O4) nanoparticles. Photocatalysis and Fenton reaction products were measured using a multiscatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Compared with Fe 3 O 4 alone, MF showed a stronger UV–vis absorption, implying an enhanced catalytic activity. This was probably due to the cocatalytic reaction mediated by the Mo 4+ /Mo 6+ redox couples. After the ZnO loading, MFZ had optimal absorbance at 652 nm, which was mainly attributed to the presence of ZnO nanoparticles. , Interestingly, we found that the absorbance at 652 nm strengthened with increasing temperature, suggesting that a high temperature promoted the production of • OH (Figure B). The resulting oxTMB solution had enhanced absorbances at 652 nm with the increase of MFZ concentrations (Figure C).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with Fe 3 O 4 alone, MF showed a stronger UV–vis absorption, implying an enhanced catalytic activity. This was probably due to the cocatalytic reaction mediated by the Mo 4+ /Mo 6+ redox couples. After the ZnO loading, MFZ had optimal absorbance at 652 nm, which was mainly attributed to the presence of ZnO nanoparticles. , Interestingly, we found that the absorbance at 652 nm strengthened with increasing temperature, suggesting that a high temperature promoted the production of • OH (Figure B). The resulting oxTMB solution had enhanced absorbances at 652 nm with the increase of MFZ concentrations (Figure C).…”
Section: Resultsmentioning
confidence: 85%
“…20−24 After the ZnO loading, MFZ had optimal absorbance at 652 nm, which was mainly attributed to the presence of ZnO nanoparticles. 51,52 Interestingly, we found that the absorbance at 652 nm strengthened with increasing temperature, suggesting that a high temperature promoted the production of • OH (Figure 2B). The resulting oxTMB solution had enhanced absorbances at 652 nm with the increase of MFZ concentrations (Figure 2C).…”
Section: Evaluation Of Catalytic Performancementioning
confidence: 89%